An operant blocking interpretation of instructed insensitivity to schedule contingencies. - Otto, Terri L.; Torgrud, Laine J.; Holborn, Stephen W. (Psychological Record)
Undergraduates pressed computer keys to move a cursor through a visual matrix under a multiple fixed ratio 18/differential-reinforcement-of-low-rate 6-s schedule. In Experiment 1, instructions to “Go Fast” or “Go Slow” produced schedule-insensitive performances for the majority of participants. Subsequent manipulations designed to increase reinforcer magnitude and to place social contingencies on effective cursor movement failed to undermine instructed insensitivity. Such instructed insensitivity may be caused by operant blocking, that is, response-rate instructions prevented acquisition of control by stimulus features associated with the reinforcement schedule. In Experiment 2, participants showing original compliance with response-rate instructions were exposed to the schedule contingencies without instructions. Participants thus exposed to both reinforcer points and schedule-discriminative stimuli were unlikely to show insensitivity upon reintroduction of the instructions, consistent with an operant blocking interpretation of insensitivity. The importance of examining instructional effects in terms of basic principles of stimulus control was emphasized. Reprinted by permission of the publisher.